RESIDENT SUPPORT FOR TOURISM AMIDST COVID-19 PANDEMIC IN BROMO TENGGER SEMERU NATIONAL PARK, INDONESIA: A CLUSTER ANALYSIS APPROACH - Nugroho, Prasetyo; Susanto, Denni; Nugroho, Adi; Gumilar, Edwin; Zamorano, Ivan; Atmojo, Jangkung Tri (Media Konservasi, 2022)
National parks (NPs) have become a rapidly growing segment of nature-based tourist destinations. However, the COVID-19 pandemic has impacted tourism activities across Indonesian NPs. While existing studies have scrutinized the impact of COVID-19 on tourism, studies that focused on clustering residents adjacent of NPs to support tourism amidst the COVID-19 pandemic remain underexplored. To unveil how residents are clustered, we assess residents in Ngadisari and Wonokitri villages based on their distinctive opinions of perceived benefits (PB), perceived costs (PC), perceived health risks (PHR), and support for tourism (ST). Totally, 354 respondents were obtained. We found that residents are clustered into two clusters named tourism supporters and cautious supporters. Tourism supporters are identified by their high agreement on PB and ST, and low agreement with PC. In contrast, Cautious supporters hold lower agreement in PB and ST, and higher agreement on PC and PHR. Our findings revealed that residents are heterogeneous and constitute a distinctive group of opinions and interests. Therefore, the design of policies and interventions should be adjusted based on those clusters. Key words: national park, perceived health risk, social exchange theory